Pemberdayaan Perkumpulan Penyandang Disabilitas Klaten (PPDK) Melalui Branding dan Pemasaran digital untuk Peningkatan Pemasaran Produk Karya Difabel - Susilo, Dahlan; Yuliyanto, Arif; Dawami, Angga Kusuma; Ashsidiq, Muhammad Fadhlan Ravi (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2025)
The main problem faced by PWDs called Perkumpulan Penyandang Disabilitas Klaten (PPDK) in Klaten is the limited access to information and marketing opportunities for their products, resulting in the products being known only at the local level. Therefore, training on adequate product photography and the use of digital platforms such as social media and websites are essential to increase the visibility of their products in the global market. This community service aims to increase the empowerment of people with disabilities in Klaten through the application of branding and pemasaran digital strategies in marketing products made by difables. The service method applied includes training on product photography, utilization of cloud servers for data and information management, and pemasaran digital to introduce products made by people with disabilities to the wider community. The results of this service are expected to improve the quality of product photos, expand market reach, and build a strong brand identity for difable products. The success of this training is important to open wider economic opportunities for people with disabilities and increase public awareness about the importance of equality in economic opportunities. In conclusion, pemasaran digital and branding are key to strengthening the position of people with disabilities in a larger and global market